The Influence of Using Solar System Learning Videos on Discussion Skills and Concept Understanding of Grade VI Students of SDN 37 Bengkalis in Science Learning - Saniati; Musnar Indra Daulay; Ramdhan Witarsa (Institute of Educational, Research, and Community Service, 2024)
This study aims to determine the influence of using solar system learning videos on the discussion skills and conceptual understanding of sixth-grade students at SDN 37 Bengkalis in science learning. The research employs an experimental method with a pretest-posttest control group design. The population of this study includes all sixth-grade students at SDN 37 Bengkalis, while the sample consists of two randomly selected classes. One class serves as the experimental group using the learning videos, and the other class acts as the control group using conventional teaching methods. Data were collected through tests measuring discussion skills and conceptual understanding before and after the treatment. Data analysis was conducted using t-tests and Mann-Whitney tests. The results indicate that the use of solar system learning videos significantly enhances students' discussion skills and conceptual understanding compared to conventional teaching methods. Therefore, learning videos can be an effective alternative teaching medium to improve the quality of science education in elementary schools.